ANTIATTICIST η 6 VALENTE (ἡσύχιος): A PROPOSAL FOR A DIFFERENT TEXTUAL ARRANGEMENT. (December 2021) - Tribulato, Olga
Abstract : The Antiatticist lexicon has a short lemma on the adjective ἡσύχιος 'silent, quiet' which has suffered heavy shortening and possibly interpolation. The present article argues that the text of this lemma should be edited as it stands in cod. Coisl. 345 and should not be changed. The entry and the mutual relationship between the words it includes should be assessed in the light of the Antiatticist 's approach to classical Greek, and of the Byzantine reception of the lexicon and its contents.